TP53 Is a Potential Target of Juglone Against Colorectal Cancer: Based on a Combination of Molecular Docking, Molecular Dynamics Simulation, and In Vitro Experiments - Yunting Deng; Yanan Zhang; Xinghai Chen; Weiming Wang; Jinhai Huo (Current Issues in Molecular Biology)
Background: Colorectal cancer is the third most common cancer worldwide, accounting for about 10% of all cancer cases. There is an urgent need to improve treatment outcomes and survival rates for colorectal cancer. Juglone is an anthraquinone with anti-inflammatory, antiviral, and anti-cancer properties that have shown promise in inhibiting tumor cell growth. Objectives: This study aims to explore the mechanism behind Juglone’s anti-cancer effects on colorectal cancer. Methods: Network pharmacology, molecular docking and molecular dynamics simulation were used to explore the specific targets of Juglone in the treatment of colorectal cancer. For in vitro validation, we used the CCK–8 (Cell Counting Kit–8) method, flow cytometry, ROS (Reactive Oxygen Species) detection, and Western blot analysis to assess the survival ability of colorectal cancer cells and validate the expression of proteins most closely associated with the pathways. Results: Network pharmacology identified TP53 as a key target of Juglone, involved in anti-tumor pathways. Molecular docking and molecular dynamics simulations showed that the p53 has strong affinity and stability with Juglone. Results from cytotoxicity experiments, flow cytometry, ROS detection, and Western blotting indicated that the anti-colorectal cancer effect of Juglone depends on concentration and is mediated by promoting intracellular ROS generation and upregulating the expression level of p53 protein, thereby inhibiting the progression of colorectal cancer. Conclusions: Juglone can achieve anti-colorectal cancer effects by increasing ROS levels and regulating the p53 protein.